Fostering global well-being: a new paradigm to revitalize agricultural and rural development. - Bathrick, David D. (International Food Policy Research Institute, 1998)
As the world prepares for the new millennium, all countries are trying quickly to adjust to changing needs within the increasingly mobile global marketplace. After years of structural biases and general disinterest in the developing world’s agricultural sector, global trade is now forcing poorer, agrarian-based economies to assess their natural comparative advantages and quickly adapt. Almost revolutionary structures, policies, and strategies are now required to meet such challenges. While the view taken here emphasizes that the changes under way offer considerable opportunities, it also recognizes that many producers and rural residents lack the relevant experiences, skills, and financial support to adjust to the new conditions. To make the decisive shift toward markets, national governments must become convinced that fundamental structural changes are in their national interests. Accepting this will not always be easy, and in that regard donors will need to play more aggressive and vigilant roles. Producers, the private sector and agribusiness investors, NGOs, and universities in developed and developing countries will also have to play mutually beneficial roles. David Bathrick addresses a number of conceptual themes for formulating the 21st century’s agricultural development paradigm.